Pengaruh Solvabilitas, Profitabilitas, dan Umur Perusahaan terhadap Audit Delay pada Perusahaan sektor Consumer Cylicals yang Terdaftar di Bursa Efek Indonesia tahun 2020-2022 - Elsa Fandora; Sri Rahayu; Yudi Yudi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This research aims to determine the influence of solvency, profitability, and company age on audit delay in companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange from 2020 to 2022. This study is quantitative in nature. The sample was taken using Purposive Sampling, consisting of 25 companies out of 157 companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange during 2020-2022, resulting in 75 analyzed data points. The analytical techniques employed included descriptive statistics and multiple linear regression analysis. The data was processed using SPSS version 26 for Windows. Solvency was measured using Debt to Asset Ratio (DAR), profitability was measured using Return on Asset (ROA), and company age was measured by subtracting the year of the study from the year the company was listed on the Indonesia Stock Exchange. The partial results of this research indicate that profitability and company age have an influence on audit delay, while solvency does not affect audit delay in companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange.Keywords: Audit delay, Solvency, Profitability, Company age.